Analysis of individual lawsuits on supplying medication in Sao Joao da Boa Vista, Sao Paulo, Brazil - Cabral, Ildelisa; Rezende, Laura Ferreira de [UNESP] (Univ Sao Paulo, 2015)
This study seeks to analyze the individual lawsuits filed to guarantee access to medication in the city of Sao Joao da Boa Vista, Sao Paulo State, Brazil. It is a longitudinal retrospective study that examines documents from 2009 to 2012 to analyze the lawsuits filed by individuals against the city government to receive supplies of medication. A total of 87 lawsuits were analyzed, and the following results were found: individual injunctions filed by women beneficiaries of the gratuity of righteousness, with sponsorship from private lawyers, in which the defendant is the director of the Municipal Department of Health. Through private prescriptions, the women solicited name-brand medications not listed by the Brazilian Public Health System (SUS), all of which are registered with the Brazilian National Health Surveillance Agency (Anvisa). The results obtained are compatible with those found in the literature. It can be concluded that, to guarantee individuals' constitutional right to health it is necessary a better organization of the State regarding pharmaceutical assistance.
Keywords: Brazilian Public Health System; Lawsuits; Legalization; Medications